Toll-Like Receptors -2, -3, -4 and -7 Expression Patterns in the Liver of a CLP-Induced Sepsis Mouse Model. Issue 2 (7th February 2020) - Aravanis, Chrysostomos V.; Kapelouzou, Alkistis; Vagios, Stylianos; Tsilimigras, Diamantis I.; Katsimpoulas, Michalis; Moris, Demetrios; Demesticha, Theano D.; Schizas, Dimitrios; Kostakis, Alkiviadis; Machairas, Anastasios; Liakakos, Theodore
ABSTRACT: Objective : To investigate the expression of toll-like receptors (TLRs) in the liver of septic mouse model. Materials and methods : For this study seventy-two C57BL/6J mice were utilized. Sepsis was induced by cecal ligation and puncture (CLP) in the mice of the three septic (S) groups (euthanized at 24 hours, 48 hours and 72 hours). Sham (laparotomy)- operated mice constituted the control (C) groups (euthanized at 24, 48 and 72 hours). Blood samples were drawn and liver tissues were extracted and examined histologically. The expression of TLRs 2, 3, 4 and 7 was assessed via immunohistochemistry (IHC) and qrt-PCR (quantitative- Polymerase Chain Reaction). Results : Liver function tests were elevated in all S-groups in contrast to their time-equivalent control groups (S24 versus C24, S48 versus C48 and S72 versus C72) ( p < 0.05). Liver histology displayed progressive deterioration in the septic groups. IHC and qrt-PCR both showed an increased expression of all TLRs in the septic mice in comparison to their analogous control ones ( p < 0.05). Analysis of livers and intestines of the septic animals proved that all TLRs were significantly expressed in higher levels in the intestinal tissues at 24h and 48h ( p < 0.05) except for TLR 3 in S48 ( p > 0.05); whereas at 72 hours only TLR 4 levels were significantly elevated in the intestine ( p < 0.05). Conclusion : TLRs seem to be expressed in significant levels in the livers of septic rodents, indicating that they have a possible role in the pathophysiology of liver damage in septic conditions.